Trend Pemanfaatan Media Sosial sebagai Upaya Pengembangan UMKM di Taman Olahraga Silampari - Oktarendah, Fatma; Tunut, Susyanto; Nadea, Salma; Bangsawan, Arubina (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to analyze the trend of social media utilization as a strategic effort to develop Micro, Small, and Medium Enterprises (MSMEs) in the Silampari Sports Park (TOS) in Lubuklinggau City. Methodology/approach: This study used a descriptive qualitative approach with 80 MSME samples from the TOS area. Data were collected through interviews, observations, and questionnaires to explore the use of social media, marketing strategies, and economic impact. Results/findings: The results indicate that 67.5% of MSMEs use social media for digital marketing, mainly Instagram (42%), Facebook (35%), and TikTok (22%). Social media marketing led to an average sales increase of 45.3%, particularly in the culinary and fashion sectors. Conclusion: Social media boosts MSME performance in TOS Lubuklinggau with a 45.3% sales increase, especially in culinary and fashion. This study reveals the potential of digital marketing and the need for wider adoption and stakeholder support. Limitations: This study is limited by its specific sample, potential qualitative bias, and focus on MSMEs that already use social media. Contribution: This study offers a model and practical recommendations to support MSME digital marketing and accelerate local business digital transformation.